CD64 and I/T Ratio as a Diagnostic Test on Neonatal Sepsis in Banjarmasin - Dewi Indah Noviana Pratiwi; Pandji Winata Nurikhwan; Muhammad Naufal Firdaus (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2024)
Neonatal sepsis remains a major problem in the service and care of neonates. The clinical features of neonatal sepsis are non-specific, which makes it difficult to diagnose. The primary objective of this study was to assess the clinical use of cluster of differentiation 64 as a diagnostic marker of neonatal infection. This research used an analytical observational study. The research subjects consisted of 43 samples of neonates at Ulin Hospital, Banjarmasin who had met the inclusion criteria. The results of the study concluded that there was no significant difference between the I/T ratio and cluster of differentiation 64 values in patients with suspected neonatal sepsis with the gold standard procalcitonin and/or blood culture at Ulin Hospital with p=0.874 for the I/T ratio and p=0.285 for cluster of differentiation 64. The diagnostic test for the I/T ratio with a cut-off of 0.2 showed a sensitivity of 23.8%, specificity of 72.7%, positive predictive value of 45.5%, negative predictive value of 50%, mean of 0.16, and median of 0.11. The results of the cluster of differentiation 64 diagnostic test with a cut-off of 2025 showed a sensitivity of 42.9%, specificity of 72.7%, positive predictive value of 81.8%, negative predictive value of 50%, mean of 2487.93, and median of 1671. There was no significant difference between the I/T ratio and cluster of differentiation 64 values in patients with suspected neonatal sepsis with the gold standard procalcitonin and/or blood culture at Ulin Hospital, Banjarmasin.